L’adolescence est-elle soluble dans l’enfance ? Définitions et délimitations du public en littérature et culture de la jeunesse - Adrienne Boutang (Transatlantica)
This paper deals with youth culture, focusing on literary, film, and television works. It examines the distinction between two types of audiences, namely children and teenagers, in contemporary popular culture, addressing both the production and reception of the works. It brings out the defining features which characterize these two audiences, through a multidisciplinary approach that pertains to psychology, cultural studies, and narratology. The purpose of this study is to delineate the field of youth culture by contrasting it with productions targeting family audiences.